Naravni potenciali regij in njihova raba - Vovk Korže, Ana (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
Negative impact of activities on nature, natural resources and human environment occur because of natural resources misuse. Studies of vulnerability plan to modify natural resources because of influence of different activities. Geographical aspects in those studies are not presented well enough because of narrow sector interests, that diminish the importance of environment. Use of natural potential is presented on ground of biotope with the case study of contact region Dravinjske gorice, between Pannonian and alpine region.
Keywords: kulturna krajina; pokrajinska ekologija; raba tal; Slovenia; Slovenija; sonaravni razvoj; sustainable development; trajnostni razvoj